Episodic Future Thinking: Linking Neuropsychological Performance with Episodic Detail in Young and Old Adults. Issue 9 (September 2013) - Cole, Scott N.; Morrison, Catriona M.; Conway, Martin A.
Episodic future thinking (EFT) has been linked with our ability to remember past events. However, its specific neurocognitive subprocesses have remained elusive. In Experiment 1, a study of healthy older adults was conducted to investigate the candidate subprocesses of EFT. Participants completed a standard EFT cue word task, two memory measures (Verbal Paired Associates I, Source Memory), and two measures of executive function (Trail Making Test, Tower Test). In Experiment 2, healthy young adults also completed an EFT task and neuropsychological measures. The link between neurocognitive measures and five characteristics of EFT was investigated. Specifically, it was found that Source Memory and Trail Making Test performance predicted the episodic specificity of future events in older but not younger adults. Replicating previous findings, older adults produced future events with greater semantic but fewer episodic details than did young adults. These results extend the data and emphasize the importance of the multiple subprocesses underlying EFT.